Phase-sensitive radioluminescence and photoluminescence features in Tm3+-doped yttrium tantalates for cyan and white light generation - Labaki, Hayra do Prado; Caixeta, Fábio José [UNESP]; Marques, Natasha Policei; José Guidelli, Éder; Rocha Gonçalves, Rogéria (Royal Society of Chemistry (RSC), 2022)
Radioluminescence and visible photoluminescence tunability features from a single Tm3+-doped yttrium tantalate phosphor prepared by a soft sol-gel method designed to afford cubic Y3TaO7 and monoclinic M′-YTaO4 crystalline phases are reported. The annealing temperature influenced the crystallization kinetics and stabilized a preferential phase. To investigate how the crystalline phase affected the Tm3+ optical properties, excitation and emission spectra in the visible range were recorded for the samples annealed at 900 or 1100 °C. Inhomogeneous broadening in the emission spectra was due to the structural disorder of the Y3TaO7 phase. Energy transfer between the yttrium tantalate host and Tm3+ ions was observed upon CT band excitation. Under UV light, an intense and tunable cyan to blue emission ascribed to both the Tm3+ transitions 1D2 → 3F4 and 1G4 → 3H6 also emerged and could be observed by the naked eye. The lifetime decay curves demonstrated the occupation of distinct sites and that the symmetry sites occupied by Tm3+ ions in the Y3TaO7 host have higher lifetime values than in the M′-YTaO4 phase. A radioluminescence study was carried out to evaluate the yttrium tantalate scintillation performance, which was considerably enhanced in the presence of the M′-YTaO4 phase. Intense white light emission displaying a large color correlated temperature range could be obtained by controlling the delay time for the time-resolved measurements and upon an orange-emitting phosphor addition. All the above-mentioned structural and photoluminescence properties make these Tm3+-doped yttrium tantalates potential candidates for photonic applications, particularly integrated w-LED systems.